Implementasi Algoritma Negascout Untuk Permainan Checkers - Aditya Kurniawan Effendi; Rosa Delima; Antonius Rachmat Chrismanto (Jurnal Informatika, 2012)
Checker is a zero sum game which means if one player is declared win then the other player is declared lose, if one player gets 1 point then the other player gets -1 point. In this type of game every player have full knowledge of other player condition, like every move the other player has, what kind of pawn and the position of other player's pawn. This game will be implemented with Negascout and compared to Alpha-Beta to see wether it offer better or worse performance than Alpha-Beta. Both algorithm will be given 5 identical board condition to solve and the search depth will be limited to 4, 6 and 8 level. The result showed Negascout outperformed Alpha-Beta on 86% of the test performed. It searched less node than Alpha-Beta especially with depth 8. The result also showed Negascout found one difference node solution compared to Alpha-Beta with identical heuristic score. Negascout returned identical heuristic score with Alpha-Beta on all test. Kata Kunci : Negascout, Permainan, Checkers, Kecerdasan Buatan